Organocatalytic Heterocyclization Driven by Dynamic Kinetic Resolution: Enantioselective Access to Multi‐heteroatomic Cyclic Structures Mediated by Cinchona Alkaloid‐based Catalysts. Issue 16 (20th June 2017) - Capaccio, V.; Capobianco, A.; Stanzione, A.; Pierri, G.; Tedesco, C.; Di Mola, A.; Massa, A.; Palombi, L.
Abstract: A new class of multi‐heteroatomic cyclic compounds containing N, S and O has been achieved in an enantioselective fashion via desymmetrization of 2‐cyano‐N‐tosylbenzylidenimine with thiols and subsequent catalytic dynamic kinetic resolution (DKR). Both organo‐ and phase transfer catalysis based on cinchona alkaloids having two H‐bonding coordination sites proved to be effective to furnish very good level of enantioselectivity (up to 95:5 er ) in the heterocyclization of racemic N‐Tosyl‐protected N, S‐acetals deriving from 2‐formyl benzonitriles. Abstract :